Chronological Review of Endoscopic Indices in Inflammatory Bowel Disease - Joon Seop Lee; Eun Soo Kim; Won Moon (Korean Society of Gastrointestinal Endoscopy, 2019)
Inflammatory bowel disease (IBD) is considered a chronic condition characterized by mucosal or transmural inflammation in the gastrointestinal tract. Endoscopic diagnosis and surveillance in patients with IBD have become crucial. In addition, endoscopy is a useful modality in estimation and evaluation of the disease, treatment results, and efficacy of treatment delivery and surveillance. In relation to these aspects, endoscopic disease activity has been commonly estimated in clinical practices and trials. At present, many endoscopic indices of ulcerative colitis have been introduced, including the Truelove and Witts Endoscopy Index, Baron Index, Powell-Tuck Index, Sutherland Index, Mayo Clinic Endoscopic Sub-Score, Rachmilewitz Index, Modified Baron Index, Endoscopic Activity Index, Ulcerative Colitis Endoscopic Index of Severity, Ulcerative Colitis Colonoscopic Index of Severity, and Modified Mayo Endoscopic Score. Endoscopic indices have been also suggested for Crohn's disease, such as the Crohn's Disease Endoscopic Index of Severity, Simple Endoscopic Score for Crohn's Disease, and Rutgeerts Postoperative Endoscopic Index. However, most endoscopic indices have not been validated owing to the complexity of their parameters and inter-observer variations. Therefore, a chronological approach for understanding the various endoscopic indices relating to IBD is needed to improve the management.